Study on the electrical conductivity of In-doped SrTiO3 with B-site deficiency prepared by sol–gel method. (11th September 2019) - Li, Runping; Zhang, Cheng; Liu, Jianhua; Zhou, Junwen; Xu, Lei
Abstract: In-doped SrTiO3 with B-site deficiency was synthesised by sol–gel method. The effects of B-site deficiency on the weight loss, phase, microstructure and electrical properties of Sr(Ti0.9 In0.1 )1− x O3− δ ( x = 0, 0.02 and 0.04) samples are investigated. The solid solution is formed at 1016 °C. Sr(Ti0.9 In0.1 )1− x O3− δ powders sintered at 1400 °C for 5 h in air exhibit a single-phase cubic perovskite structure. The total electrical conductivity initially increases and then decreases with further increase in the temperature. The conductivity of Sr(Ti0.9 In0.1 )0.96 O3− δ reaches the maximum value of 0.0158 S cm −1 at 400 °C.